Rearing laying hens: the effect of aviary design and genetic strain on pullet exercise and perching behavior - Rentsch, Ana K.; Harlander, Alexandra; Siegford, Janice M.; Vitienes, Isabela; Willie, Bettina M.; Widowski, Tina M. (Frontiers in Animal Science, 2023)
To prepare laying hens for life in cage-free aviaries, they must be reared in aviaries that accustom them to the challenges of navigating a complex three-dimensional structure. Rearing aviaries vary in design and contain a brooding compartment in which chicks are confined during the first six weeks of age. These compartments vary greatly in their size and complexity. The present study aimed to examine the impact of environmental complexity during early life and birds’ genetic strain on their space use and forms/types of exercise. Four consecutive flocks of brown and white chicks were raised in three styles of rearing aviary with low, intermediate, or high complexity. Behavioral observations were performed at three ages during the brooding phase (weeks 1, 3, and 5) and the open phase when the brooding compartments were opened (weeks 7, 11, and 17). Behaviors observed were categorized as aerial locomotion, perching, dynamic load-bearing behavior (DLB), and wing-involved load-bearing behavior (WLB). During the brooding phase, chicks in aviaries of high complexity exercised most frequently (e.g., DLB events/minute: 1.75 in High vs 1.11 in Mid and 0.10 in Low, p<0.0001), and the effect remained for whites, but not the browns, during the open phase. White pullets exercised more than brown pullets both in brooding (e.g., 1.47 vs 1.28 DLB events/minute, p<0.0001) and open phases in High and Mid (e.g., 1.17 vs 0.93 DLB events/minute, housing x stain interaction p=0.009). Throughout rearing, whites had higher odds of perching than browns (brooding: 0.52 vs 0.45, p=0.04, open: 0.27 vs 0.17, p=0.0007). We concluded that rearing aviary design can affect behavior during the brooding phase; however, once the brooding compartments were opened, housing differences almost exclusively affected white pullets. The data suggest that genetic strain of birds must be considered in the design of pullet housing with the goal of maximizing space use and musculoskeletal development of laying hen pullets.